QUALITY OF SERVICE BASED MULTICASTING ROUTING PROTOCOLS FOR MANETS: A SURVEY - Sahu, Prabhat Kumar; Pattanayak, Binod Kumar (APTIKOM Journal on Computer Science and Information Technologies, 2017)
The modern electronic age consists of many new approaches for the communication among the humancivilizations and the AD HOC network is one of the successful self-configuring and infrastructure-lesscommunicating approach. Mobile ad hoc networks (MANETs) comprised of mobile nodes organize themselves insuch a manner that the can move freely inside the network and frequently change their position. Open architectureand dynamic nature of the network enhance its use in multimedia applications that needs graphics, audio, data,image, video and animation. Now a day?s the increasing use of multimedia and Internet technology needs quality ofservice (QoS) in MANETs in order to provide better service for the companies. This type of applications lendsthemselves well to multicast operations. As multicasting supports group oriented computing it can improve the QoSof the wireless medium by means of sending multiple copies of packets by exploring the internet broadcast propertiesof wireless transmission. Hence QoS multicasting plays a great role in MANETs for multimedia applications.However it is very difficult and challenging task to provide QoS multicasting. With unique features and by means ofdifferent recovery mechanisms, many researchers have been proposed various QoS based multicasting routingprotocols for MANETs. In order to assist QoS multicasting routing protocols design for MANETs, we characterizethe taxonomy of the multicast routing protocols and design features in this paper.